Risk factors and diagnosis of flat adenomas of the colon. (February 2011) - Anderson, Joseph C
In addition to histology, size and location, a morphologic description can be ascribed to polyps and adenomas. Traditionally, adenomas have been described as sessile and pedunculated, but it is now accepted that they can also present as flat or even depressed. Although first recognized in 1985, flat adenomas have become more common in Western published literature and in endoscopic reports. The Japanese Research Society Classification describes flat adenomas as lesions with a height that is less than one half of the diameter, while the Paris classification divides polyps into protruding and nonprotruding. The clinical significance of flat adenomas includes their potential malignancy, difficulty in detection and possible role in interval cancers. Serrated polyps represent a subset of polyps that have all the features that make flat lesions clinically important. Due to the relatively recent recognition of these lesions, as well as the technology required to detect them, the prevalence and malignant potential of these lesions in Western patients are still unknown. Finally, the best techniques and equipment for detecting flat polyps are also not established. In this article, we examine the issue of flat polyps and their significance in colorectal cancer screening with regard to prevalence, risk factors and methods for detecting flat polyps.